Influence of Elemental Sulfur on Nutrient Uptake, Yield and Quality of Cucumber Grown in Sandy Calcareous Soil - Motior, M.R.; Abdou, A.S.; Al Darwish, F.H.; El-Tarabily, K.A.; Awad, M.A.; Golam, F.; Sofian-Azirun, Mohd (2011)
This study was carried out to investigate the effect of elemental sulfur (S 0) and sulfur oxidizing bacteria (Paracoccus versutus) on nutrient uptake, yield and quality of cucumber grown in sandy calcareous soils. Both elemental sulfur powder (S 0P) and pellets of sulfur powder-Tiger 90 (S 0T) were applied at rates of 0, 1, 5 and 10 t/ha at Al Hamraneya. On the contrary, S 0P was used at rates of 0, 1, 5 and 10 t/ha combined with or without Paracoccus versutus (Pv) at Al Kuwaitat, United Arab Emirates (UAE). Higher concentrations of N, P, S, Mn and Zn in leaves and yield of cucumber at both locations were obtained with application of S 0 at rates of 5 and 10 t/ha. Total soluble sugar (TSS) content and vitamin C was higher with the application of S 0 at rates of 5 and 10 t/ha. Application of Pv individually or with varying levels of S 0P had no positive effect on nutrients uptake, yield and quality of cucumber. A positive correlation was observed between shelf life and vitamin C. At Al Hamraneya S 0P performed better than S 0T. The results reveal that application of S 0P at the rate of 5 t/ha in sandy calcareous soils can enhance the nutrients uptake ability, increase yield and superior quality of cucumber at both locations in UAE.